The Poem of Experience: Term and Foundations - Alahmad, Mouhamad Basher Yaser (Journal of Humanities & Social Sciences, 2021)
This research, with its cognitive tools, seeks to present its understanding of the term "poem of experience", according to a vision based on the approach between thematic poetry that is defined by themes and purposes emanating from an accident, and poetry that revolts against this stereotype, and transcends the occasion and the topic, to be concerned with their impact and effectiveness. The research attempted to draw the boundaries of the term "poem of experience" by examining the lexical significance and the deliberative context of the term. He also noted the confusion of some critical studies between the terms "experiment" and "experimentation" with regard to the sensitivity of experience and the formality of experimentation, and concluded the general foundations of the poem experience, which is reflected in the destruction of topics, transgression of purposes, diversity of significance and openness of interpretation. Hence, the research acquires its legitimacy, based on proposing a critical concept specific to the modernist poem, which is no longer bound by the stereotyped poetic controls and its functions.
Keywords: the poem of experience; experimentation; objectivity; poetic purposes; non-objective